Geometrical and algebraic approach to multiple representations - Ozkan, Erdoan Mehmet; Tepedeldiren, Y. Tayfun; Unal, Hasan (ELSEVIER SCIENCE BV, 2011)
Recently, the use of multiple representations in teaching math has gained great importance. Why it is important? The answer to this question is not complicated. When we try to teach a mathematical concept to any level of students, we first must know the background of them. So that we can easily establish a good understanding of the concept. This can be achieved perfectly if the class contains the same level of students. But this is not always possible. It is hard to find the ideal teaching enviroment. This mainly depends on the students and we still say that it is important to know their level of math and how much relation can be established for their past experiences to learn a new concept. As it is clear that the most problematic lesson is math. Is there any way of teaching math to the students that has any level of mathematical background? The answer is Yes. The name of the method is Multiple Representation. It is defined as to teach the mathematical concept in more than one form (Ainsworth, Bibby, Wood, 2002). In this study we are mainly interested in geometrical and algebraic approach. We also evaluate the background of the students for learning process. (C) 2011 Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: Simplifications; The Expected Background; Simple Sample Explanation; Conditional forms; Education & Educational Research